2014
DOI: 10.1017/s0031182014000122
|View full text |Cite
|
Sign up to set email alerts
|

The communities of helminth parasites ofHeterandria bimaculata(Teleostei: Poeciliidae) from the upper Río La Antigua basin, east-central Mexico show a predictable structure

Abstract: We investigated a basic generalization in parasite community ecology stating that stochastic processes played a major part in determining the composition of helminth communities of freshwater fish, or on the contrary, if these communities are predictable, diverse and structured species assemblages. We determined the species pool of helminth parasites of a tropical freshwater fish Heterandria bimaculata in its heartland, the upper Río La Antigua basin in east-central Mexico. Approaching our data from the metapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
14
2
Order By: Relevance
“…Com.). Interestingly and significantly there is empirical evidence that tropical fishes do have a range of autogenic specialists which explains high degrees of similarity between localities [34]. However, a metacommunity study of helminth parasites of eels in the River Exe system [16] also demonstrated the presence of a range of autogenic specialists which, in this case, did not confer similarity between localities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Com.). Interestingly and significantly there is empirical evidence that tropical fishes do have a range of autogenic specialists which explains high degrees of similarity between localities [34]. However, a metacommunity study of helminth parasites of eels in the River Exe system [16] also demonstrated the presence of a range of autogenic specialists which, in this case, did not confer similarity between localities.…”
Section: Discussionmentioning
confidence: 99%
“…However, a metacommunity study of helminth parasites of eels in the River Exe system [16] also demonstrated the presence of a range of autogenic specialists which, in this case, did not confer similarity between localities. The difference seems to be the role of the acanthocephalans that tend to dominate freshwater fish parasite communities at northern temperate latitudes [16, 17] and that are very uncommon and generally occur at low prevalence and abundance levels, and certainly do not dominate tropical assemblages [34 and present work].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our goal was to explore the factors that might contribute to the richness and coexistence of helminth parasites of P. bimaculatus across 11 localities in the La Antigua River, a neotropical system in Veracruz, Mexico. Populations of the poeciliid P. bimaculatus in the La Antigua River were chosen for the present study because some aspects of their parasite community structure have been described previously, including information on common and rare species (Salgado-Maldonado et al, 2014); however, information on community saturation, intraspecific and interspecific aggregation, and consistency of pairwise species associations is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Urocleidoides vaginoclaustrum was originally described from introduced aquarium fish X. hellerii in India; however, recently studies had been expanded its distribution to others hosts in Mexican drainages. So far, it has been found infecting mainly poeciliids, such as, X. hellerii (Mendoza-Franco et al, 2015;Mendoza-Palmero & Aguilar-Aguilar, 2008), Pseudoxiphophorus bimaculata (Salgado-Maldonado et al, 2014), X. malinche and X. birchmanni (present work), but recently it had been recorded from the profundulid Profundulus labialis (Mendoza-Franco et al, 2015).…”
Section: Discussionmentioning
confidence: 66%